The power of mentoring : shaping people who will shape the world - Sanders, Martin (Camp Hill, Pa. : Wing Spread Pub., 2009)
Mentoring is the indispensable tool in the spiritual and character formation of today's emerging leaders. With biblical examples of mentors and insights from experts in discipleship and mentor training, this book provides practical strategies, exercises, and models for your journey through mentoring.
Keywords: Mentoring in church work